A comparative synthesis of UK mathematics education research: what are we talking about and do we align with international discourse?. Issue 1 (2nd January 2021) - Marks, Rachel; Foster, Colin; Barclay, Nancy; Barnes, Alison; Treacy, Páraic
ABSTRACT: This paper makes an important and original contribution to the updating of methodological approaches to research syntheses. We analysed all 813 Proceedings of the British Society for Research into Learning Mathematics from 2003 to 2018, first using a quantitative corpus-survey and qualitative thematic coding and, again, independently, using topic modelling. We found strong convergence between findings from the different methods. We compare our findings to those from an earlier Proceedings review (1995–2002) and to a recent review of the corpus of publications in the Journal for Research in Mathematics Education and Educational Studies in Mathematics, as well as to a review by the European Society for Research into Learning Mathematics and several other reviews. We found considerable similarity between the issues discussed, and similar trends over time. We conclude that the efficiency of topic modelling makes it a powerful option to include among a range of methodological approaches to research review.